CFO Compensation: Evidence from Australia - Duong, Lien; Evans, John (Elsevier, 2015)
We investigate the extent to which the incentive alignment theory and the managerial power theory explain the variability of CFO compensation in Australia. We find a positive relationship between the level of CFO compensation and measures of job complexity and firm stock market performance. However, we do not find the pay-for-performance link when performance is measured at the CFO-specific level. CFOs actually receive higher non-cash compensation when reporting quality is lower, suggesting a sharp contrast to predictions of the incentive alignment approach. Conversely, we find that CFOs who have more managerial power (the CFO is on the board of directors, or holds a higher level of stock ownership, or stays longer in their position) receive significantly higher compensation. For example, a CFO who has board membership receives on average $323,590 more than the total compensation of a CFO who is not a board insider. Overall both theories are important in determining Australian CFO compensation but the managerial power hypothesis explains a larger fraction of variation in CFO pay than the incentive alignment view.